Esporte escolar: aspectos pedagógicos e de formação humana - Sawitzki, Rosalvo Luis (Universidade do Vale do Rio do Sinos, 2007)
The sholastic sportive practice and the shcool games are activities that make presents in daily of the schools, involving the students, professors, educational directors, parents, employees, politicians and community in general. Such activities must be planned, executed and evaluated as according to a educational politics, based on educational and pedagogical presupposed. The present study was developed with the objective to analyze the planning and the sportive practice in the lessons of physical education, the internal games of the school and in the games between schools in the context of the educational politics and the political-pedagogic project from a public school of the Rio Grande do Sul`s estate, considering the aspects of formation human being and development of the citizenship. The metodologyc process consisted of a study of case, in the qualitative perspective, with observation in loco of the development of the esportive practice and the internal school games of the school and school games between
Keywords: cidadania; desenvolvimento social; formação humana; jogos escolares; política educacional; prática esportiva; citizenship; community development; educational politcs; formation human being; school games; sportive practice; Ciências Humanas